RNA Vaccines: A Suitable Platform for Tackling Emerging Pandemics? - Sandbrink, Jonas B.; Shattock, Robin J. (Frontiers in Immunology, 2020)
The COVID-19 pandemic demonstrates the ongoing threat of pandemics caused by novel, previously unrecognised, or mutated pathogens with high transmissibility. Currently, vaccine development is too slow for vaccines to be used in the control of emerging pandemics. RNA-based vaccines might be suitable to meet this challenge. The use of an RNA-based delivery mechanism promises fast vaccine development, clinical approval, and production. The simplicity of in vitro transcription of mRNA suggests potential for fast, scalable, and low-cost manufacture. RNA vaccines are safe in theory and have shown acceptable tolerability in first clinical trials. Immunogenicity of SARS-CoV-2 mRNA vaccines in phase 1 trials looks promising, however induction of cellular immunity needs to be confirmed and optimised. Further optimisation of RNA vaccine modification and formulation to this end is needed, which may also enable single injection regimens to be achievable. Self-amplifying RNA vaccines, which show high immunogenicity at low doses, might help to improve potency while keeping manufacturing costs low and speed high. With theoretical properties of RNA vaccines looking promising, their clinical efficacy is the key remaining question with regard to their suitability for tackling emerging pandemics. This question might be answered by ongoing efficacy trials of SARS-CoV-2 mRNA vaccines.